Mitigation strategies for blasting-induced cracks and vibrations in twin-arch tunnel structures - Xianshun Zhou; Jin Chen; Xuemin Zhang; Kai Zhu; Yanyong Zhang; Jianbo Fei; Muhammad Irslan Khalid (Defence Technology)
Due to space constraints in mountainous areas, twin tunnels are sometimes constructed very close to each other or even overlap. This proximity challenges the structural stability of tunnels built with the drill-and-blast method, as the short propagation distance amplifies blasting vibrations. A case of blasting damage is reported in this paper, where concrete cracks crossed construction joints in the twin-arch lining. To identify the causes of these cracks and develop effective vibration mitigation measures, field monitoring and numerical analysis were conducted. Specifically, a restart method was used to simulate the second peak particle velocity (PPV) of MS3 delays occurring 50 ms after the MS1 delays. The study found that the dynamic tensile stress in the tunnel induced by the blast wave has a linear relationship with the of the product of the concrete wave impedance and the PPV. A blast vibration velocity exceeding 23.3 cm/s resulted in tensile stress in the lining surpassing the ultimate tensile strength of C30 concrete, leading to tensile cracking on the blast-facing arch of the constructed tunnel. To control excessive vibration velocity, a mitigation trench was implemented to reduce blast wave impact. The trench, approximately 15 m in length, 50 cm in width, and 450 cm in height, effectively lowered vibration velocities, achieving an average reduction rate of 52% according to numerical analysis. A key innovation of this study is the on-site implementation and validation of the trench's effectiveness in mitigating vibrations. A feasible trench construction configuration was proposed to overcome the limitations of a single trench in fully controlling vibrations. To further enhance protection, zoned blasting and an auxiliary rock pillar, 80 cm in width, were incorporated to reinforce the mid-wall. This study introduces novel strategies for vibration protection in tunnel blasting, offering innovative solutions to address blasting-induced vibrations and effectively minimize their impact, thereby enhancing safety and structural stability.